Evaluation of aqueous extracts of de-oiled cakes and organic manures on Trichoderma harzianum growth under in vitro conditions - Rao, V Govardhan; Ambadkar, C V; Navgire, K D Navgire; Apet, K T; Sonttake, P L (Indian Journal of Plant Protection, 2022)
Different aqueous extracts of de-oiled cakes and organic manures at 10 and 15 per cent concentrations were evaluated on Trichoderma harzianum under in vitro condition. Among nine aqueous extracts at 10 per cent concentration, neem cake enhanced the maximum mycelial growth (69.04 mm) followed by mustard cake (69.07 mm). Third and fourth superior treatments were safflower cake (63.73mm) and groundnut cake (63.48mm) at 3 and 5 days after inoculation (DAI) with a mean enhancement of 22.19 and 22.18 per cent respectively. However, the remaining organic amendments soya cake, cotton cake, vermicompost, goat manure and poultry manure recorded comparatively less mean growth enhancement (21.11, 13.35, 15.75, 15.86 and 14.92 %) at both the concentrations tested respectively. Moreover, the next increased concentration at 15 per cent also increased the rate of growth enhancement with all the de-oiled cakes and organic manures in same order of merit as like 10 per cent concentration.